Inositols in Midlife - Sanjay Kalra; Bharti Kalra (Wolters Kluwer Medknow Publications, 2018)
This review describes the mechanistic, animal, and clinical data related to the use of inositols in midlife. It covers studies related to the mechanism of action of myo-inositol and D-chiro-inositol and randomized controlled trials conducted in postmenopausal women with metabolic syndrome and supports these data with the results of in vitro and animal studies on inositol in nephropathy and other related conditions. Recent advances related to biochemistry, pharmaceutical science, and genetics are discussed. It concludes that inositols have a potential role to play in maintaining metabolic health in postmenopausal women.